(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Among the numerous techniques of drawing of the rupestral engravings, it is a which more particularly held attention. They are the naviformes heavy losses. These engravings appear under a shape disentangled in both extremities, blown in the center and profoundly dug. The biggest can reach several tens centimeters in length. They were obtained by successive scratchings of walls, made by the height downward as the lines show it which overflow at feet of engravings. It seems that these scratchings are made with a cutting tool, a knife for example. A large number of engravings appears under the shape of signs with which it was besides shown that they could be codified. We can see a cultural unity there that will be needed safe to look for but that the archaeology has already proved in Cerdagne. We can ask from then on legally the question of the sense of these engravings. Do we have to make, with these repetitions of symbols, for a real synonymy?